Perilaku Swamedikasi pada Perokok di Indonesia - Via Dolorosa Halilintar; Amal Chalik Sjaaf (Media Kesehatan Masyarakat Indonesia, 2020)
Self-Medication practices are considered to be a quick solution in treatment when a person can not access the formal health services, but on the other hand, this behavior can cast up the economic burden and health losses if not properly monitored. Meanwhile, smoking is seen as a negative behavior, which can also cause a double burden, both in terms of increased expenditure also has a negative effect on health. This study aims to describe self-medication behavior among smokers in Indonesia and the determinants that influence it. This study is a quantitative study using secondary data from the Indonesia National Socio-Economic Survey (SUSENAS) in 2017. The observation unit is individuals, and the sample criteria are smokers with the probability of doing self-medication due to health problems. The number of analyzed samples was 53.317 respondents. Descriptive analysis is used to see the prevalence of self-medication among smokers. Logistic regression is used to see the determinants that influence a smoker's decision to make self-medication. The results of the follow-up analysis showed that most smokers did Swamedikasi (75.99%). The level of education (p=0,005) and ownership of health (p=0,000) insurance has a significant effect on self-medicated behavior. Through this research, it is expected to be material for learning and advocating about behavior in seeking treatment for smokers.